A Web Based Expert System for SMT Diagnostics in PCB Assembly Manufacturing - Kumaravel, Munisamy (2006)
In today's manufacturing environment, Real-time monitoring, diagnosis, control and process optimization is needed to be competitive. Manufacturers need to capture knowledge about their processes and apply it in a way that can effectively drive real-time operational decisions. They also need to apply knowledge that detects and diagnoses process problems early and then helps operators recover quickly so that production can be kept going. This study involves the development of a prototype web based expert system for aiding manufacturing floor operators in solving their daily routine problems. The main aspect of the program is to help operators in areas such as CAD, PROCESS and TEST in their daily hassles. The engineering knowledge is stored in the knowledge base in the form of production rules (IF/THEN), while the facts of the problem are stored in the form of knowledge base. The reasoning processes are located in the inference engine. The backbone of the system was implemented using two web based programming language html and Java. The image and animation has been developed using Flash 8.0 and Adobe Photoshop 9.0, while the database is developed primarily in rule based text file ( *.kb ).